Leisure participation for school-aged children with Down syndrome - Oates, A.; Bebbington, A.; Bourke, J.; Girdler, Sonya; Leonard, H. (Informa Healthcare, 2011)
Purpose.To describe leisure participation for school-aged children with Down syndrome and to investigate how factors, classified by the World Health Organisation's International Classification of Functioning, Disability and Health, influence their leisure participation. Method.Families in Western Australia with a child aged 518 years with Down syndrome were surveyed in a population-based study (n=208) in 2004. Results.One-third of parents reported that their child with Down syndrome had no friends although half reported two or more friends. Factors affecting number of friendships included the child's functional ability, behavioural issues and parent's availability of time. Those children with higher functional independence scores in daily tasks were more likely to have two or more friends than those with lower functional independence scores (OR: 1.02, 95% CI 1.011.04 for a single point increase in WeeFIM score). All children participated in predominantly solitary and sedentary leisure activities. Conclusions.Leisure participation was affected by complex factors both within and external to the child with Down syndrome. Further investigation of the relevance of these factors to leisure may enable more satisfying and meaningful participation in leisure for school-aged children with Down syndrome. © 2011 Informa UK, Ltd.